### 4 Answers

Relevance

- ?Lv 76 months ago
d...............d.............dy

--- (f(y)) = --- (f(y)) • ---............ANS (Option D)

dx.............dx...........dx

- ted sLv 76 months ago
Yes D) is correct ; .....df / dx ≡ ( df / dw ) ( dw / dt ) (dt/dx) by the theorem on derivatives of Composite Functions...in algebra you remember that [ A B C } / [ B C H ] ≡ A / H...same holds for derivatives using ' symbols '

- ?Lv 76 months ago
The Chain Rule: dz/dx = (dz/dy)•(dy/dx)

So, where f = f(y), df/dx = (df/dy)•(dy/dx)

d(f(y))/dx = (d(f(y))/dy)•(dy/dx)

Answer D

Still have questions? Get your answers by asking now.